source : e-eduanswers.com

## If f(x) = x2 – 2x and g(x) = 6x + 4, for which value of x does (f + g)(x) = 0? -4

-2

2

4

(f + g)(x) = 0 if value of x= -2

Step-by-step explanation:

f(x)=x^2-2x and g(x)=6x+4 then find

(f+g)(x)=0

We know that (f+g)(x)=0 is equal to f(x)+g(x)=0

Solving:

f(x)+g(x)=0

x^2-2x+(6x+4)=0

x^2-2x+6x+4=0

x^2+4x+4=0

Now factorizing to find value of x

x^2+2x+2x+4=0

x(x+2)+2(x+2)=0

(x+2)(x+2)=0

x+2=0 and x+2=0

x=-2 and x=-2

So, (f + g)(x) = 0 if value of x= -2

Keywords: Composition of functions

Learn more about Composition of functions at:

#learnwithBrainly

Given f(x) = 6x – 2 and g(x) = 6x – 1, evaluate the – How to solve: Given f(x) = 6x – 2 and g(x) = 6x – 1, evaluate the composite function. fg(0) By signing up, you'll get thousands of step-by-step… for Teachers for Schools for Working ScholarsIf f(x) = x2 – 2x and g(x) = 6x + 4, for which value of x does (f + g)(x) = 0 – 6229196Solution for F(x)=x2+6x+5 equation: (F)=F2+6F+5 We move all terms to the left: (F)-(F2+6F+5)=0 We add all the numbers together, and all the variables-(+F^2+6F+5)+F=0 We get rid of parentheses-F^2-6F+F-5=0 We add all the numbers together, and all the variables-1F^2-5F-5=0 a = -1; b = -5; c = -5; Δ = b 2-4ac Δ = -5 2-4·(-1)·(-5) Δ = 5 The delta value is higher than zero, so the equation has

If f(x) = x2 – 2x and g(x) = 6x + 4, for which value of x – g(x) = cos(x/2) – 3x f(x) = 2x + 5 g(f(x)) = cos(f(x)/2) – 3f(x) = cos(2x+5)/2 – 3(2x+5) = cos(2x+5)/2 -6x-15Free equations calculator – solve linear, quadratic, polynomial, radical, exponential and logarithmic equations with all the steps. Type in any equation to get the solution, steps and graphThe Algebra of Functions . Like terms, functions may be combined by addition, subtraction, multiplication or division. Example 1. Given f ( x ) = 2x + 1 and g ( x ) = x2 + 2x – 1 find ( f + g ) ( x ) and ( f + g ) ( 2 )

F(x)=x2+6x+5 – Get Easy Solution – Correct answers: 1 question: If f(x) = x2 – 2x and g(x) = 6x + 4, for which value of x does (f + g)(x) = 0? -4 -2 2 4We have the function g with a single variable. So we could replace it back to x: g(x) = 3x – 5. So the question becomes much simpler: f(x) = 2x. g(x) = 3x – 5. To find f(g(x)), just put in g(x) = 3x – 5 into f(x) f(x) = 2x. f(g(x)) = 2 * g(x) f(g(x)) = 2(3x – 5) f(g(x)) = 6x – 10. Answer: 6x – 10. g(x+2)=3x+1Free math problem solver answers your algebra, geometry, trigonometry, calculus, and statistics homework questions with step-by-step explanations, just like a math tutor.